Personal Social Networks of Community-Dwelling Oldest Old During the Covid-19 Pandemic—A Qualitative Study - Kulmala, Jenni; Tiilikainen, Elisa; Lisko, Inna; Ngandu, Tiia; Kivipelto, Miia; Solomon, Alina (Frontiers in Public Health, 2021)
The COVID-19 pandemic and its related restrictions have affected the everyday life of older people. Advanced age is a significant predisposing factor for a more severe COVID-19 infection, increasing the risk for hospitalization and mortality. Even though restrictions have been, thus, well-grounded, they may also have had detrimental effects on the social well-being of older people. Personal networks and social activity are known protective factors against the premature decline in health and functioning, and it is widely acknowledged that social isolation increases feelings of loneliness, poor quality of life, and even the risk for diseases and disabilities among older adults. This qualitative study investigated changes in personal networks among community-dwelling oldest-old individuals (persons aged 80 and over) during the first and second waves of the COVID-19 pandemic in Finland. The data is part of the Cardiovascular Risk Factors, Aging, and Dementia (CAIDE85+) study, which is an ongoing large longitudinal population-based study in Finland. In this qualitative sub-study, we analyzed fifteen in-depth telephone interviews using directed content analyses and identified five types of changes in personal social networks during the pandemic. In type 1, all social contacts were significantly reduced due to official recommendations and fear of the virus. Type 2 included modified ways of being socially active i.e., by deploying new technology, and in type 3, social contacts increased during the lockdown. In type 4, personal social networks were changed unexpectedly or dramatically due to a death of a spouse, for example. In type 5, we observed stable social networks, which had not been affected by the pandemic. At an individual level, one person could have had different types of changes during the pandemic. These results highlight the heterogeneity of the oldest olds' personal social networks and changes related to them during the exceptional times of the COVID-19 pandemic. Social activity and personal networks play an important role in the well-being of the oldest old, but individual situations, needs, and preferences toward personal social networks should be taken into account when planning social activities, policies, and interventions.